Isolated limb perfusion with the tumor‐targeting human monoclonal antibody–cytokine fusion protein L19‐TNF plus melphalan and mild hyperthermia in patients with locally advanced extremity melanoma1. Issue 2 (4th June 2012) - Papadia, Francesco; Basso, Valeria; Patuzzo, Roberto; Maurichi, Andrea; Di Florio, Annabella; Zardi, Luciano; Ventura, Elisa; González‐Iglesias, Reinerio; Lovato, Valeria; Giovannoni, Leonardo; Tasciotti, Annaelisa; Neri, Dario; et al.
Abstract Background L19‐TNF is a tumor‐targeting immunocytokine composed of the human L19 antibody binding to extra domain B (ED‐B) of fibronectin of newly formed blood vessels, and of human TNF. This exploratory trial evaluates safety and clinical activity of L19‐TNF plus melphalan‐containing isolated limb perfusion (ILP) in extremity melanoma patients. Methods Seven and 10 patients received 325 µg and 650 µg of L19‐TNF, respectively, during the ILP. Patients were studied for safety, tolerability, and clinical activity of this experimental L19‐TNF ILP procedure. Results Non‐hematologic toxicity of L19‐TNF ILP was very low, but severe myelosuppression was seen in four patients. Although L19‐TNF was administered at a TNF‐equivalent dose of only 3.13 and 6.25% of the approved TNF (Beromun®) dose of 4 mg, L19‐TNF ILP induced objective responses in 86 and 89% of patients, respectively, including a complete response (CR) in 5/10 patients treated with L19‐TNF ILP at 650 µg that was durable at 12 months in four patients. No CR was seen at 325 µg of L19‐TNF. Conclusions ILP with L19‐TNF had a favorable safety and a promising activity profile at a dose of 650 µg of L19‐TNF, supporting the exploration of higher L19‐TNF doses and a Phase II trial comparing L19‐TNF ILP with standard melphalan‐containing ILP. J. Surg. Oncol. 2013;107:173–179. © 2012 Wiley Periodicals, Inc.